The Predictive Ability Of Big Five Personality On Motivational Orientation States Among Pre-Service Teachers - Ooi, Soo Yuan (2018)
The purpose of the current study is to identify the predictive ability of Big Five Personality on the motivational orientation states in Self Determination Theory (SDT) among the pre-service teachers in the Malaysian Teacher Education Institutes (Institut Pendidikan Guru, IPGs). Besides, the study is interested in identifying the best Big Five personality factor that shows highest level of self-determination as well as the best personality model to explain self-determination among the pre-service teachers in the IPGs. The rationales of this study are observed from two different perspectives, which are the situational and literatures from both the international and Malaysian contexts. It is clear from both the current practice and the literatures that further research is needed to delve deeper into the understanding of motivations from the perspective of Self Determination Theory (SDT), especially among Malaysian pre-service teachers. Literatures have demonstrated the vital roles motivational orientation states and personality have in the education field. Data for this study is collected using survey questionnaire, utilizing the General Causality Orientations Scale (GCOS) and the NEO Five Factor Inventory 3 (NEO FFI 3). The pre-service teachers are selected through stratified and cluster sampling from the 27 IPGs in Malaysia.